Investigating e-WOM via TikTok Impact on Purchase Intention: Brand “S” - Arie Setiawan; Teresa Gabriella; Wulan Darmawan; Yuli Rakasiwi (Ranah Research : Journal of Multidisciplinary Research and Development, 2024)
This journal investigates the impact of social media marketing, particularly on TikTok, on the purchase intention of skincare products among Indonesian young adults, with a focus on the case study of skincare brand "S". The research employs a descriptive causal approach and utilizes the Technology Acceptance Model (TAM) and Information Adoption Model (IAM) as theoretical frameworks. The study explores the dimensions of information quality, quantity, credibility, and needs on TikTok, emphasizing its influence on consumer behavior. The findings of information quality, quantity, credibility, and needs indicate positive and significant relationships between these dimensions, highlighting the role of TikTok in shaping consumer decisions. But, information quantity indicates a negative relationship to purchase intention. Specifically, high-quality and credible information, along with addressing consumer needs, contribute to enhanced information usefulness, adoption, and ultimately purchase intention. The research underscores the strategic importance of skincare brands tailoring their TikTok marketing to deliver targeted, high-quality, and credible content that addresses specific consumer needs. Additionally, building and sustaining credibility on TikTok, particularly through authentic reviews, is crucial for fostering consumer trust. Overall, the study emphasizes a holistic approach for brands to maximize the impact of their digital marketing strategies on driving online sales and influencing purchase intentions.